Diagnostic utility of medical thoracoscopy in T cell lymphoblastic lymphoma presenting with pleural effusion. (2021) - Mehta, Asmita A.; Shafi, Tajik M.; Nambiar, Ajit; Pavithran, Keechilat
Abstract: Adult lymphoblastic lymphoma (LBL) is an aggressive form of non-Hodgkin lymphoma occurring among predominantly adolescent and young adult men, accounting for 1%–2% of all non-Hodgkin's lymphomas. In contrast to B-LBL, T-cell LBL is much more common, accounting for up to 90% of disease in adults. Mediastinal mass, pleural and/or pericardial effusions are the major characteristics of T-LBL. We report an 27-year-old male with a pleural effusion, mediastinal lymphadenitis, and a normal hemogram. The cytology of the pleural effusion initially was lymphocytic exudative and ADA was high. For definitive diagnosis a medical thoracoscopy was done. The partial pleura showed multiple irregular nodules and thickening in sheets. It was picked and immunophenotypic study revealed the following: CD3, TdTþ, CD7 with Ki 67 index of 70–80%. The patient was finally diagnosed with T-LBL. He was treated with chemotherapy and is on regular follow up with resolution of effusion. The case highlight the point that medical thoracoscopy is a safe and accurate diagnostic procedure for pleural diseases, and partial pleura biopsy yielded the correct diagnosis.